2015
DOI: 10.1167/15.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Implicit motor learning is impaired in strabismic adults

Abstract: Binocular vision disorders (BVD) are quite common in subjects with cerebellar dysfunctions. Also individuals with strabismus often suffer from many motor deficits, such as impaired body balance and walking. It is known that the cerebellum is necessary to maintain proper body posture but also to learn motor skills. It is conceivable that subjects with BVD would also have deficits in procedural (implicit) motor learning, one of the primary cerebellar functions. The primary aim of this study was to explore motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Due to the small sample available, we did not distinguish between binocular and nonbinocular subjects, but it is important to note that most of our anisometropic amblyopes had stereopsis, and most of our strabismic amblyopes were nonbinocular observers and manifested deeper amblyopia as compared to the anisometropic group from our previous research (Perdziak et al, 2014). It is commonly known that the lack of binocular vision affects not only visual but also a variety of other functions related to visuomotor coordination (Grant & Moseley, 2011;Suttle, Melmoth, Finlay, Sloper, & Grant, 2011) and motor control abilities (Przekoracka-Krawczyk, Nawrot, Czaińska, & Michalak, 2014;Przekoracka-Krawczyk, Nawrot, Kopyciuk, & Naskręcki, 2015). It was found that nonbinocular subjects (usually strabismic amblyopes) tend to have poorer optotype and Vernier acuity than those with residual binocular function (usually anisometropic amblyopes;McKee et al, 2003).…”
Section: Increased Saccadic Latencymentioning
confidence: 96%
“…Due to the small sample available, we did not distinguish between binocular and nonbinocular subjects, but it is important to note that most of our anisometropic amblyopes had stereopsis, and most of our strabismic amblyopes were nonbinocular observers and manifested deeper amblyopia as compared to the anisometropic group from our previous research (Perdziak et al, 2014). It is commonly known that the lack of binocular vision affects not only visual but also a variety of other functions related to visuomotor coordination (Grant & Moseley, 2011;Suttle, Melmoth, Finlay, Sloper, & Grant, 2011) and motor control abilities (Przekoracka-Krawczyk, Nawrot, Czaińska, & Michalak, 2014;Przekoracka-Krawczyk, Nawrot, Kopyciuk, & Naskręcki, 2015). It was found that nonbinocular subjects (usually strabismic amblyopes) tend to have poorer optotype and Vernier acuity than those with residual binocular function (usually anisometropic amblyopes;McKee et al, 2003).…”
Section: Increased Saccadic Latencymentioning
confidence: 96%
“…This, in turn, could be reflected by low adaptation rate and inability to fully reduce fixation disparity. The idea that the cerebellum may be involved in controlling VPA and other oculomotor deficits was also suggested in other studies which demonstrated impaired ability of implicit motor learning (one of the fundamental cerebellar functions) in subjects with binocular problems [56] and dyslexia [40], poor body balance control in adults [57] and children [58] with strabismus or changes in walking strategies applied by patients with strabismus [59]. All of these functions depend, at least to some extent, on cerebellar control.…”
Section: Discussionmentioning
confidence: 88%
“…Several investigations have reported dyslexic readers with deficits in vergence and other oculomotor function (Bucci, Brémond-Gignac, & Kapoula, 2008;Bucci, Nassibi, Gérard, Bui-Quoc, & Seassau, 2012;Kapoula & Bucci, 2007;Legrand, Bui-Quoc, Doré-Mazars, Lemoine, Gérard, & Bucci, 2012;Przekoracka-Krawczyk, Brenk-Krakowska, Nawrot, Rusiak, & Naskręcki, 2017). In addition, studies on strabismic patients also suggest dysfunction in the cerebellum (Gaertner, Creux, Espinasse-Berrod, Orssaud, Dufier, & Kapoula, 2013;Przekoracka-Krawczyk, Nawrot, Kopyciuk, & Naskrȩcki, 2015). Collectively, these lines of research indicate that the cerebellum is part of the neural circuit needed to mediate vergence eye movement function.…”
Section: Researchers Have Developed Several Paradigms Tomentioning
confidence: 98%
“…Previous clinical studies have demonstrated that phoria adaptation is reduced in patients with binocular dysfunction such as convergence insufficiency (Brautaset & Jennings, 2005a;Brautaset & Jennings, 2006;Henson & North, 1980;North & Henson, 1981;Schor & Horner, 1989;Sreenivasan & Bobier, 2014), exotropia (Kiyak Yilmaz, Kose, Yilmaz, & Uretmen, 2015;Zahavi, Friling, Ron, Ehrenberg, Nahum, & Snir, 2019), convergence excess esotropia (Garretty, 2018;Wygnanski-Jaffe, Trotter, Watts, Kraft, & Abdolell, 2003), and decompensated heterophoria (Przekoracka-Krawczyk, Michalak, & Pyżalska, 2019). In addition, there is evidence that therapeutic interventions such as vision therapy (Brautaset & Jennings, 2006) or surgery (Akbari, Mehrabi Bahar, Mirmohammadsadeghi, Bayat, & Masoumi, 2018;Garretty, 2018) may lead to an improvement in phoria adaptation in some patients.…”
Section: Clinical Relevancementioning
confidence: 99%